dy/dx = (y-1)^2 given the initial condition y(0) =1 find an explicit solution.(adsbygoogle = window.adsbygoogle || []).push({});

separation of variables gives:

(y-1)^-2 dy = dx

integrating both sides I get

-(y-1)^-1 = x + c

-1= (y-1)(x+c)

-1/(x+c) = y - 1

y= 1 - 1/(x+c) but how can the intial condition work?

no value of c will make 1= 1 - 1(0+c)

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Perplexed by this simple problem Please help

**Physics Forums | Science Articles, Homework Help, Discussion**